2021
DOI: 10.3389/ffgc.2021.672909
|View full text |Cite
|
Sign up to set email alerts
|

“The Forest Has Become Our New Living Room” – The Critical Importance of Urban Forests During the COVID-19 Pandemic

Abstract: Out of nowhere the COVID-19 pandemic has turned people’s everyday lives upside down. Public places in urban areas were closed. However, leaving the house for recreational and leisure purposes in nature was still allowed in Germany – even during lockdown in March and April of 2020. As a result, urban forests have gained unprecedented importance – not only for recreational activities, but also for maintaining social contacts and coping with psychological stress. With these diverse requirements, many people have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 54 publications
1
50
1
1
Order By: Relevance
“…The lower number of forest visitors in 2016 could be associated with other factors, such as socioeconomic characteristics and or climate. These factors could be studied in-depth to get to the gist of the discussion [66][67][68][69][70][71][72]. We conclude that, ceteris paribus, the studied data showed a notable trend in the COVID-19 lockdown period with special attention in March, April, and May 2021.…”
Section: Results Of Field Researchmentioning
confidence: 97%
See 3 more Smart Citations
“…The lower number of forest visitors in 2016 could be associated with other factors, such as socioeconomic characteristics and or climate. These factors could be studied in-depth to get to the gist of the discussion [66][67][68][69][70][71][72]. We conclude that, ceteris paribus, the studied data showed a notable trend in the COVID-19 lockdown period with special attention in March, April, and May 2021.…”
Section: Results Of Field Researchmentioning
confidence: 97%
“…The lower number of forest visitors in 2016 could be associated with other factors, such as socioeconomic characteristics and or climate. These factors could be studied in-depth to get to the gist of the discussion [66][67][68][69][70][71][72].…”
Section: Results Of Field Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kajosaari and Pasanen (2021) found that in the Helsinki Metropolitan Area, restorative experiences took place most often near blue areas and in large (>30 ha) recreational forests. In the light of restrictions on everyday movement, the mental construction of forests as the recovery of agency and control plays an important role in high visitation of forests (Weinbrenner et al, 2021), and these factors may also play a role in higher rates of visitation to areas of high tree cover density.…”
Section: Implications For Ugi Managementmentioning
confidence: 99%